ENHANCING THE STUDENTS’ SPEAKING SKILL IN SPEAKING CLASS PROGRAM THROUGH ROLE PLAY AT SENIOR HIGH SCHOOL - Henry Elisa (STKIP Persada Khatulistiwa Sintang, 2019)
Abstract: The objectives of this study were to describe the impact, strengths and weaknesses of role play in the teaching and learning process among the tenth grades students at Senior High School in Kalasan, Sleman. This study applied qualitative research. The subjects of the study were an English Teacher for Speaking Class Program and students of class XB. Techniques for collecting data for the study were observation, document review and interview. Data collection tools of the study were recorder and interview guidelines. The results of the study proved that role play has improved the teaching and learning process in speaking class program for the tenth grade students at Senior High School. The strengths of this technique in the process of teaching and learning was the teacher can bring the social situation into the classroom and the student can have new experiences in learning language by play a certain role in the speaking activity. During the process of learning, the students would be pay attention to the other students who were performed in front of the classroom and they may tried to find a way to improved their performance when their turn to perform or play the role they have got from the teachers.